Autonomous mobile robot using programmable logic controller (PLC): article - Ab Kadir, Mohd Lutfi (2006)
In the era of technology, robots are commonly used in almost all activities whether in industries or even at home. The development in robot technology has increased gradually as the time passes. Nowadays most robots are intelligent whereby they have “brain” that can sense the presence of input variables, map or locate the source of presence factor, plan for further step of actions and act according to the program being set by the programmer or Sense, Map, Plan and Act (SMPA) theory of operation [1]. This paper will explain about the software development using SYSWIN 3.4 programming Ladder Diagram tool for Omron CPM2A PLC controller and brief explanation on the hardware model.